Incitement to Violence and Stochastic Terrorism: Legal, Academic, and Practical Parameters for Researchers and Investigators - Amman, Molly (Terrorism and political violence, 2024)
In the U.S., legal incitement is generally understood as speech that is intended to incite or produce imminent lawless action, and is likely, in fact, to do so. It is an a old construct extending back to ancient Greece. In contrast, stochastic terrorism is a relatively new academic term describing an unpredicted act of targeted violence stemming from political demagoguery. Both constructs are hard problems in a liberal democratic society. How do we think about such issues of speech involving both persuasion and influence that may lead to intentional harm of others? In furtherance of understanding such historical attacks and those that may unfold in the future, we juxtapose the concepts of stochastic terrorism and incitement to violence, and define the legal, academic, and practical parameters of these concepts for researchers and investigators who are not formally trained in the law. There are points of both convergence and divergence regarding these terms, both legally and psychologically, which may help clarify their application to academic research, legal opinion, and other real world problems.